Going the Distance: Towards a new professionalism for full-time distance education faculty at the University of the Philippines - Arinto, Patricia B. (International Review of Research in Open and Distributed Learning, 2007)
Several constraints influence the formation of a professional identity by full-time distance education faculty at the University of the Philippines. One of these is the marginalisation of distance education (DE) in the academy as a consequence of DE’s identification with low status disciplines, as well as with developments in higher education that are undermining traditional academic identities. There are also constraints arising from the social organisation of distance education itself. The paper offers a (re)conceptualisation of academic professionalism for distance education faculty that is more responsive to the challenges that they face, and more empowering for themselves and the academic and other communities of which they are a part.